Cytokine gene polymorphisms and expression in Turkish pediatric cochlear implant patients - Baysal, Elif; Oğuzkan Balcı, Sibel; Çelenk, Fatih; Kahraman, Merve; Deniz, Murat; Tunç, Orhan; Durucu, Cengiz; Mumbuç, Semih; Kanlıkama, Muzaffer; Pehlivan, Sacide (ENT Updates, 2016)
Objective: We assessed the association between the polymorphisms and expressions of three cytokine genes and clinical parameters in children who underwent cochlear implantation due to profound congenital sensorineural hearing loss. Methods: We analyzed the IL-6/-174, IFN-γ/+874 and TNF-α/- 308 genes in 64 cases with congenital sensorineural hearing loss and in 70 healthy controls. Cytokine genotyping/expression was performed using the PCR-SSP method. Results: No significant differences were detected between the patient group and the healthy controls with respect to the distributions and numbers of genotypes and alleles of TNF-α or IL-6. However, the TT genotype, associated with high expression of IFN-γ, and the T allele frequency were significantly more frequent in the patient group versus the controls (p=0.016 and 0.023, respectively). Conclusion: Our results suggest that high expression of the IFN-γ gene may be associated with susceptibility to the disease. Consequently, IFN-γ may be a useful marker of the etiopathogenesis of congenital sensorineural hearing loss.